Agonista tendencioso para o receptor AT 1 exerce efeitos benéficos sobre parâmetros cardiovasculares de ratos espontaneamente hipertensos - Alves, Cristiane Rodrigues de Almeida Silva (2017)
Arterial hypertension (AH) is a disorder that results from impairment in blood pressure control mechanisms, among which the baroreflex and the Renin Angiotensin Aldosterone System (RAAS) stand out. The actions of Angiotensin II in the AT1 receptor type (AT1R) are determinants for the elevation of arterial pressure via Gq/11 protein-coupled AT1R activation. Because of this, AT1R antagonists have been good options for HA treatment, but with undesirable side effects. TRV120027 is an AT1 receptor biased agonist, in other words, it is capable of binding to AT1R without activating Gq/11 protein, but rather some MAPKs and β-arrestin, promoting cardioprotective effects. Studies point to TRV120027 as a potential drug for the treatment of heart failure, but nothing has been reported regarding the effects of this compound on hypertension. The aim of the present study was to investigate the effects of TRV120027 on arterial pressure and its autonomic modulation, baroreflex sensitivity and serum and tissue oxidative stress in normotensive Wistar Kyoto (WKY) and spontaneously hypertensive (SHR) rats. The WKY and SHR rats were divided into four groups: WKY and SHR untreated (WKY-C and SHR-C) and treated with TRV120027 (WKY+TRV and SHR+TRV). Treatment with TRV120027 was performed intracerebroventricularly using osmotic minipumps implanted towards the lateral ventricle of the animals, through which the compound was injected for 14 days (20 ng/h/day). On the 13th day, catheters were implanted in the femoral vein and artery of the animals for drug administration and evaluation of cardiovascular parameters, respectively. After that, the animals were sacrificed and blood, kidneys and liver were collected to evaluate oxidative stress by the thiobarbituric acid method. All protocols were approved by CEUA-UFPB (N. 090/2016). Treatment with TRV120027 did not change the arterial pressure of normotensive animals (WKY-C: 119 ± 3 vs. WKY+TRV: 108 ± 3 mmHg), but was effective in reducing arterial pressure in SHR+TRV animals when compared to SHR-C group (160 ± 5 vs .181 ± 3 mmHg, respectively, p <0.05), no significant difference in heart rate was observed between the groups evaluated. Treatment improved the cardiac vagal tone in SHR+TRV when compared to SHR-C (ΔHR = +83 ± 1 vs. +54 ± 3 bpm, p <0, 05), as well as improved the sympathetic vasomotor tone (ΔPAM = -47 ± 2 vs. -64 ± 5 mmHg, p< 0,05). In addition, in SHR+TRV there was an improvement in the induced (SHR-C: -1,4 ± 0,2 vs. SHR+TRV: 2,4 ± 0,3 bpm/mmHg, p<0,05) and spontaneous (SHR-C: 0,5 ± 0,1 vs. SHR+TRV: 1,8 ± 0,2, ms/mmHg, p<0,05) baroreflex sensitivity. The TRV120027 was also able to reduce serum and renal MDA levels in SHR+TRV animals when compared to SHR-C group (Serum: 0.37 ± 0.05 vs. 2.58 ± 0.08 nmol/ml; Kidneys: 8.18 ± 0.03 vs. 11.7 ± 0.05 nmol/mg organ). The results obtained demonstrate that TRV120027, acting in the Central Nervous System, is able to reduce the arterial pressure in spontaneously hypertensive rats, improve autonomic function, restore baroreflex sensitivity and reduce peripheral oxidative stress present in these animals. These data reinforce the involvement of Gq/11 protein-dependent pathway coupled to AT1R in the hypertensive process and point to beneficial potential of the biased agonist, TRV120027, against hypertension and related events by activating β-arrestin pathway-coupled to AT1R in a biased way.